Analysis of Pharmacy Installation Performance ‘Aisyiyah Islamic Hospital Nganjuk Using the Balanced Scorecard Approach - Triwidyastuti, Hety Aria; Oetari, R. A.; Harsono, Samuel Budi (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Background: The Balanced Scorecard (BSC) is a method that provides complete performance and measurement consisting of four perspectives.Objectives: The study aimed to determine the performance of the RSI 'Aisyiyah Nganjuk Pharmacy Installation using BSC and to determine a strategy map based on performance evaluation.Methods: This research is non-experimental with a descriptive design. The retrospective data was used to examine personnel files, financial reports, stock, sales, patient visits, and prescriptions from January 2019 to December 2021. The prospective data was used for questionnaires, interviews, and direct observation. The data obtained is qualitative and quantitative. Gap analysis using the Wilcoxon test with non-parametric statistical methods. Data analysis was carried out descriptively, comparing with standards and management needs to determine performance, combining SWOT analysis to determine a strategy map.Results: The financial perspective shows ITOR in 2019 (5.84%), 2020 (4.01%), 2021 (4.63%), GROS in 2019 (0.13%), 2020 (-0.18), 2021 (0.02%), GPM in 2019 (33.26%), 2020 (43.67%), 2021 (34.23%). The internal business perspective shows that the availability of medicine has yet to reach 100%, completeness of Medicine Information Services 34.54%, dispensing time of compounded medicine 43.10 minutes, non-compounded 24.40 minutes, and 100% absence of medication errors. The growth and learning perspective show high results in job satisfaction, morale, productivity, employee turnover, and the need for MIS development. The customer perspective shows reasonable customer satisfaction but still low patient connectivity.Conclusion: Several indicators still do not meet the standards, so they need to be developed with the S-O strategy.